Faglig internationalisme før Anden Verdenskrig: Anden del: Amsterdam Internationalens politik og strategi 1919-1940 - Knudsen, Knud (Arbejderhistorie - tidsskrift for historie, kultur og politik, 2012)
Knud Knudsen: Trade Union Internationalism before the Second World War, Part Two, Arbejderhistorie 1/2012, s. 48-65. The article deals with the politics and strategy of the social democratic International Federation of Trade Unions (IFTU – also known as the Amsterdam International) for the period 1919-40. In the first years after its reconstitution in 1919 the Amsterdam International had a comparatively activist profile. Anti-communism became a pronounced part of this political profile of the Amsterdam International: the trade unions should not be organs for revolution. Amsterdam distanced itself from the use of physical force in the trade union struggles and accused the communist Red International of Labour Unions (RILU) of being subordinate to national and political interests. Unlike the trade union international before the Great War the Amsterdam International had a broader trade union political profile. From the beginning it engaged itself in the peace movement and to an increasing extent the cause of disarmament and from the mid-1920s the primary strategy rested on seeking influence on the system of the League of Nations – embracing the ILO – which was established at the end of the War. The Amsterdam International formulated its own economic and sociopolitical programmes, which were put forward to the League of Nations and the ILO. During the economic crisis of the 1930s the chief political themes were: a shortening of the working day (a 40 hour week), public work projects, and state planning. After the Nazis had come to power in Germany in 1933 – which resulted in the disbanding of Europe`s largest trade union movement – it was the main political themes, especially the fight against fascism and war, that dominated the trade union International. It is a chief premise in the article that throughout the whole period the Amsterdam International worked on the basis of and in relation to the League of Nations` system first established in 1919-20. The same nationalistic forces that undermined the League also lay behind the impotence of the Amsterdam International.